Popularization of cars, penetration of electric vehicles, and energy consumption of Chinese households - Yin, Siyuan (Frontiers in Energy Research, 2024)
Based on survey data from Chinese households, this study uses a fixed effects model to examine the impact of car ownership on household energy consumption. The results show that car purchases lead to a significant 46% increase in household energy consumption costs. Purchasing cars leads to a 108% increase in household transportation expenditure (including gasoline expenditure), showing a significant direct effect, while heating costs increase by 17.1%, 12.0%, and 23.3%, respectively, representing an indirect effect. Furthermore, in regions with rapid EV growth, EVs have alleviated the promotion of cars in energy consumption, which is conducive to achieving the goal of carbon neutrality. This study helps provide measures to reduce future household energy consumption and promote the realization of carbon neutrality.